The Visibility of Scholarly Knowledge: Awareness for Open Access in Hacettepe University - Korhan Levent Ertürk; Mehmet Emin Küçük (Türk Kütüphaneciliği)
The scholars begin to place their works into the open repositories or open access journals as well as their personal web sites. In the international arena, the open repositories contain a total of 14,000 Turkey-based scholarly contents. The focus of this study is to determine the level of awareness for open access concept of scholars in Hacettepe University. An electronic questionnaire was conducted to scholars. The data were collected through questionnaire from full time academic staff member in Hacettepe University. It was found that 50% of scholars are aware of the open access concept and 92% of the scholars are willing to place their works into the institutional repository of their university. According to questionnaire study result, different types of works such as articles and assertions can be placed in the institutional open repositories in Turkey and their functionality can be increased in a short time.